PERANCANGAN KEDARURATAN MEDIS DI SEKOLAH DASAR NEGERI 017 SAMBOJA - Zulfikar, Iwan; Mulya, Widya; Reski, Ajeng (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
Medical emergencies at school are temporary relief and treatment efforts on victims at school before being taken to hospitals, health centers, or health clinics for better help from doctors or paramedics. The purpose of the study was to design a medical emergency at Kamboja public elementary school 017. This study is a quantic study with triangulation techniques and is analyzed descriptively. The data used is primary data from interviews and observations, secondary data derived from the company. Results of research for the design of medical emergencies include creating SOPs, creating response time emergencies, simulating the application of medical emergency responses, and evaluating the completeness of medical facilities. First aid training in accidents (first aid) or basic first aid as a provision of knowledge and ability in case of an emergency in school. Conclusions were made the implementation of emergency response SOPs, the conformity of medical facilities in accordance with PERMEN No.15 / MEN / VIII / 2008, providing first aid training in accidents, and making response time emergency. Advice for public primary school 017 is to provide accident relief training on all staff and teachers in schools on a scale and make cooperation with medical authorities, health centers, clinics, and/or nearby hospitals for follow-up in the event of an emergency. Keywords: Emergency, Emergency response, Medical Emergency